796 A phase I/II trial combining avelumab and trabectedin for advanced liposarcoma and leiomyosarcoma. (9th November 2020) - Wagner, Michael; He, Qianchuan; Zhang, Yuzheng; Cranmer, Lee; Loggers, Elizabeth; McDonnell, Sabrina; Maxwell, Shannon; Pollack, Seth
Abstract : Background: Leiomyosarcoma (LMS) and liposarcoma (LPS) are soft tissue sarcoma subtypes that frequently express PD-L1 and are infiltrated with T cells. They are generally resistant to PD-1/PD-L1 inhibition, possibly due to infiltration with high levels of immunosuppressive tumor-associated macrophages (TAMs). Trabectedin is FDA-approved for refractory LMS and LPS. Prior studies demonstrated trabectedin activity against TAMs. We hypothesized that PD-L1 inhibition by avelumab would be enhanced by trabectedin through its inhibition of immunosuppressive TAMs. Methods: This is a single-arm, open-label, Phase I/II study of avelumab combined with trabectedin for patients with advanced LMS and LPS. In the phase I portion, we evaluated safety and feasibility at 3 trabectedin doses (1, 1.2 and 1.5 mg/m2) with avelumab at standard dosing (10 mg/kg) in a 3+3 design. Primary endpoint of the phase II portion was the objective response rate (ORR) by RECIST 1.1. 24 patients were included for phase II endpoints. Secondary objectives were duration of response, progression free survival (PFS), clinical benefit rate (CBR) at 12 weeks, and overall survival. Results: 37 patients enrolled; 34 were evaluable. 23 had LMS. 11 had LPS. In Phase 1, there were DLTs in 2 of 6 patients at both higher doses of trabectedin including grade 3 GGT elevation, bilirubin and alanine aminotransferase (ALT) elevation, small bowel obstruction, and reduced ejection fraction. The recommended Phase 2 dose was 1.0 mg/m2 trabectedin and 10 mg/kg avelumab. At the Phase 2 dose, the most common adverse events (AEs) attributed to study drug were fatigue, ALT increase, diarrhea, anorexia, nausea, and infusion reaction. There were 8 instances of PORT inflammation or infection. The most common Grade 3 AEs attributed to study drug were neutropenia and ALT increase. There were no grade 4/5 AEs at the Phase 2 dose. 23 patients were evaluable for primary ORR endpoint. 2 (8.7%) had partial response (1 confirmed), 11 had stable disease as best response. CBR (PR+SD) at 12 weeks was 56%. 6 month PFS was 50.1%; median PFS is 23.4 months. 9 patients remain on study treatment. In a secondary analysis of all patients, ORR was 8.6% (3/35 with PR), median PFS was 6.1 months. Conclusions: Administration of this combination was feasible with acceptable toxicity. The recommended Phase 2 dose was 1.0 mg/m2 trabectedin and 10 mg/kg avelumab. The combination failed to meet the primary endpoint of ORR, however the PFS appears favorable compared to prior studies of trabectedin in this population and warrants further study. Trial Registration: NCT03074318 Ethics Approval: The study was approved by the Fred Hutch IRB, number 9717.